Interplay Between Tight Junctions & Adherens Junctions - Campbell, Hannah K. (Exp Cell Res, 2017)
Cell-cell adhesions are critical for the development and maintenance of tissues. Present at sites of cell-cell contact are the adherens junctions and tight junctions. The adherens junctions mediate cell-cell adhesion via the actions of nectins and cadherins. The tight junctions regulate passage of ions and small molecules between cells and establish cell polarity. Historically, the adherens and tight junctions have been thought of as discrete complexes. However, it is now clear that a high level of interdependency exists between the two junctional complexes. The adherens junctions and tight junctions are physically linked, by the zonula occludens proteins, and linked via signaling molecules including several polarity complexes and actin cytoskeletal modifiers. This review will first describe the individual components of both the adherens and tight junctions and then discuss the coupling of the two complexes with an emphasis on the signaling links and physical interactions between the two junctional complexes.